Improving Cancer MDT performance in Western Sydney - three years' experience - Lynleigh Evans; Yiren Liu; Brendan Donovan; Terence Kwan; Karen Byth; Paul Harnett (BMC, 2021)
Abstract Background While multidisciplinary teams (MDTs) are now considered an essential part of cancer care decision-making, how they perform varies widely. The authors hypothesised that a comprehensive, multipronged improvement program, and associated annual member survey, could strengthen MDT performance across a whole cancer service. Methods The study comprised the introduction of a structured program, the Tumour Program Strengthening Initiative (TPSI) linked with an annual survey of member's perceptions of their performance. Three iterations of the survey have been completed (2017, 2018 and 2019). Generalised estimating equations (GEEs) were used to test for a difference in the proportion of positive survey responses between 2017 and 2019 adjusted for team clustering. Results Twelve teams participated in TPSI. One hundred twenty-nine, 118 and 146 members completed the survey in 2017, 2018 and 2019, respectively. Of the 17 questions that were asked in all three years, nine showed significant improvement and, of these, five were highly significant. Documenting consensus, developing Terms of Reference (TORs), establishing referral criteria and referring to clinical practice guidelines showed most improvement. Questions related to patient considerations, professional development and quality improvement (QI) activities showed no significant change. Conclusions TPSI resulted in sustained and significant improvement. The MDT survey not only allowed MDT members to identify their strengths and weaknesses but also provided insights for management to flag priority areas for further support. Overall program improvement reflected the strengthening of the weakest teams as well as further improvement in highly performing MDTs. Importantly, the initiative has the potential to achieve behaviour change amongst clinicians.